2013
DOI: 10.1177/1087057113489349
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Gastric Cell-Based Assay System for Exploring Inhibitors of Octanoylated Ghrelin Production

Abstract: Ghrelin, a gastric hormone, is a growth hormone-releasing peptide. Its serine-3 acylation with octanoic acid is essential for its orexigenic activity, and therefore, inhibition of the acylation of ghrelin may help in decreasing appetite and preventing obesity. This study aimed to establish a human gastric cell-based assay system to evaluate candidate inhibitors of octanoylated ghrelin production. In human gastric carcinoma AGS cells, obligatory factors for the posttranslational modification of ghrelin, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In addition, we tested other triterpenes such as asiatic acid, glycyrrhetinic acid, and betulinic acid. The triterpenes tested above have a carboxylic acid group in a molecule similar to fatty acids that we previously reported as having an inhibitory effect on octanoylated ghrelin production [41,42]. Therefore, we confirmed that the carboxylic acid group on production of octanoylated ghrelin.…”
Section: Effects Of Triterpenes Contained In E Japonica Leaves On Ghsupporting
confidence: 76%
See 4 more Smart Citations
“…In addition, we tested other triterpenes such as asiatic acid, glycyrrhetinic acid, and betulinic acid. The triterpenes tested above have a carboxylic acid group in a molecule similar to fatty acids that we previously reported as having an inhibitory effect on octanoylated ghrelin production [41,42]. Therefore, we confirmed that the carboxylic acid group on production of octanoylated ghrelin.…”
Section: Effects Of Triterpenes Contained In E Japonica Leaves On Ghsupporting
confidence: 76%
“…AGS-GHRL8 cells expressed both GOAT and furin and produced octanoylated ghrelin in the presence of octanoic acid [41]. As shown in Figure 13, we have developed a cellbased assay system used by AGS-GHRL8 cells to screen for candidate molecules to inhibit octanoylated ghrelin production [41]. We found that fatty acids, such as heptanoic acid, stearic acid, linoleic acid, α-linolenic acid, and oleic acid, decreased octanoylated ghrelin levels [41,42].…”
Section: Effects Of Triterpenes Contained In E Japonica Leaves On Ghmentioning
confidence: 99%
See 3 more Smart Citations